ISOL Digital storytelling as a pedagogical tool for intercultural competence in EMI contexts: A case study from Southeast Asia - Lasmi Febrianingrum; Nadwa Faza Maulida Putri; Nahla J Lumpapac; Hafelatul Aisyah; Afifah Raihany (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2026)
English as a Medium of Instruction (EMI) has become widespread globally, but most studies examining its use have centered around classroom-based activities, neglecting the less explored area of how EMI works out in informal settings facilitated by peers and technology. This study investigates the involvement of Indonesian and Philippine students in intercultural collaboration through a digital storytelling project named Stories Across Borders, which lasted for one month. Six students from the secondary and tertiary levels in both countries participated in this activity involving WhatsApp chats, post-project surveys, and creation of an 18-page e-book complete with voiceovers as part of the collective book. The thematic analysis that was used to examine the intercultural learning, communication and collaboration in this data set included transcripts of WhatsApp chats, post-project reflection surveys as well as the final story. The analysis showed three themes: digital storytelling promoted the sharing and learning of each other's backgrounds with a great sense of cultural pride and empathy; online collaboration needed natural communication skills, role negotiation, and facilitation; also, EMI provided authentic stakes for confidence building but at times strategies including rephrasing and clarifying were required as dialogic meets. These findings show that digital storytelling goes beyond a mere creative practice and serves as an effective pedagogical tool for intercultural learning in EMI settings. This research extends EMI inquiries to the international level within Southeast Asian collaborations, contributing important findings for teacher education partnerships based on project-based learning and intercultural capacities with implications for educators developing global digital initiatives.